30th International Congress of Clinical Neurophysiology (Нейрофизиология, 2013)
We are happy to announce the 30th International
Congress of Clinical Neurophysiology (ICCN2014)
o f the International Federation o f Clinical
Neurophysiology (IFCN).
The ICCN2014 will take place in Berlin from March
20-23, 2014 and will be organized in conjunction with
the Annual Meeting of the German Society for Clinical
Neurophysiology and Functional Imaging (DGKN)
scheduled from March 19 -22, 2014.